Rheological and textural characteristic of restructured fruit puree - Muda, Noraziah; Barigou, Mostafa (Universiti Putra Malaysia Press, 2008)
Sago starch is a cheap form of starch which is isolated from sago palm (Metroxylon spp.) and is available in abundance in South East Asian countries. Given its low cost, Sago starch has great potential to be used as a substitute for other forms of starch. The objectives of this work were to study the effects of paste concentration on the rheological behaviour of sago starch paste, their texture properties and their freeze thaw stability compared to other types of starch. The rheological properties of sago starch were investigated at different paste concentrations (3-8 wt %). The textural properties of the samples were investigated by examining the gel strength of the samples. The percent syneresis of sago starch was also studied to examine the freeze-thaw stability of the material. The freeze thaw stability of sago starch with the addition of certain biopolymers were also characterized.